Identification of Factors Encouraging Household Consumers to Engage in Theft of Electricity in Lubumbashi, DR Congo - David, Milambo Kasumba; Bonaventure, Banza Wa Banza (Review of Industrial Engineering Letters, 2019)
Fraudulent access to the conventional electricity grid is a serious concern in developing countries. This significantly affects the revenue-generating capacity of their utilities. This article is undertaken to identify the factors encouraging the theft of electricity in Lubumbashi. Based on survey data from various municipalities in the city covering 1211 households based on a simple random sampling plan, the factors responsible for the theft of electricity were identified and ranked in order of importance. Quantitative data were subjected to one-way analysis of variance (ANOVA). In addition, a post hoc test of Tukey was applied at the significance level <5%. Qualitative data were subjected to chi-square tests. In this study, poor enforcement of the law, corruption, SNEL does not fight for the interests of real subscribers, cost of electricity, quality of service and education are the main causes encouraging electricity theft. To combat this situation it is important to put in place policies that integrate these different factors.